Painting and Sculpture from The Museum of Modern Art : catalog of Deaccessions 1929 through 1998 by Michael Asher. - Asher, Michael; Varnedoe, Kirk (New York : MoMA (The Museum of Modern Art) New York, 1999)
Afro ; Appel, Karel ; Arp, Hans (Jean) ; Avery, Milton ; Bacon, Francis ; Balla, Giacomo ; Balthus ; Baziotes, William ; Beckmann, Max ; Bell, Larry ; Belling, Rudolf ; Benton, Thomas Hart ; Berard, Christian ; Bermúdez, Cundo ; Blumenscheid, Ernest Leonard ; Bombois, Camille ; Bonnard, Pierre ; Bourgeois, Louise ; Braque, Georges ; Brauner, Victor ; Brodie, Gandy ; Brown, Joan ; Buffet, Bernard ; Calcagno, Lawrence ; Calder, Alexander ; Canadé, Vincent ; Caro, Anthony ; Cézanne, Paul ; Chadwick, Lynn ; Chagall, Marc ; Chamberlain, John ; Charlot, Jean ; De Chirico, Giorgio ; Cikovsky, Nicolai ; Cohen, George ; Cosgrove, Stanley ; Cross, Henri Edmond ; Dali, Salvador ; Daumier, Honoré ; Davie, Alan ; Davies, Arthur B. ; Davis, Stuart ; Degas, Edgar ; Delaunay, Sonia ; Delvaux, Paul ; Derain, André ; Despiau, Charles ; van Dongen, Kees ; Dove, Arthur G. ; Dubuffet, Jean ; Dupy, Raoul ; Eilshemius, Louis Michael ; Ernst, Max ; Estève, Maurice ; Fautrier, Jean ; Ferren, John ; Francis, Sam ; Fresnaye, Roger de la ; Friedman, Arnold ; Gallatin, A.E. ; Galvan, Jesus Guerrero ; Gauguin, Paul ; Glasco, Joseph ; van Gogh, Vincent ; Gorky, Arshile ; Gottlieb, Adolph ; Graham, John D. ; Gris, Juan ; Guttuso, Renato ; Hartley, Marsden ; Heckel, Erich ; Herbin, Auguste ; Hicks, Edward ; Hopper, Edward ; Isobe, Yukishisa ; Judd, Donald ; Kandinsky, Wassily ; Kantor, Morris ; Kerkam, Earl ; Kirchner, Ernst Ludwig ; Klee, Paul ; Klimt, Gustav ; Kline, Franz ; Kohn, Gabriel ; Kokoschka, Oskar ; Kolbe, Georg ; de Kooning, Willem ; Krohg, Per ; Krushenick, John ; Kuhn, Walt ; Kuniyoshi, Yasuo ; Lachaise, Gaston ; Laurencin, Marie ; Leger, Fernand ; Lehmbruck, Wilhelm ; Levi, Julian E. ; LeWitt, Sol ; Lichtenstein, Roy ; Lipchitz, Jacques ; Louis, Morris ; MacIver, Loren ; etc.
Engels
boek
Keywords: New York